2015
DOI: 10.1165/rcmb.2014-0184oc
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Is Required for Epithelial Recovery, but Not for Pulmonary Fibrosis, in Response to Bleomycin

Abstract: The pathogenesis of pulmonary fibrosis involves lung epithelial injury and aberrant proliferation of fibroblasts, and results in progressive pulmonary scarring and declining lung function. In vitro, fibroblast growth factor (FGF) 2 promotes myofibroblast differentiation and proliferation in cooperation with the profibrotic growth factor, transforming growth factor-b1, but the in vivo requirement for FGF2 in the development of pulmonary fibrosis is not known. The bleomycin model of lung injury and pulmonary fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 83 publications
2
75
0
1
Order By: Relevance
“…In addition, Lee et al25 observed the protective effects of FGF-2 in an interferon-Ī³ā€“induced emphysema mouse model. Moreover, in addition to the emphysema model, the role of FGF-2 in pulmonary epithelial recovery was also demonstrated in a bleomycin-induced pulmonary fibrosis model using FGF-2 knockout mice26.…”
Section: Experimental Backgrounds Of Lung Regeneration Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Lee et al25 observed the protective effects of FGF-2 in an interferon-Ī³ā€“induced emphysema mouse model. Moreover, in addition to the emphysema model, the role of FGF-2 in pulmonary epithelial recovery was also demonstrated in a bleomycin-induced pulmonary fibrosis model using FGF-2 knockout mice26.…”
Section: Experimental Backgrounds Of Lung Regeneration Therapymentioning
confidence: 99%
“…Because considerable evidence indicates that the major action mechanism of cell therapy is based on paracrine effects 1213161718, researchers have attempted to regenerate diseased lung with various molecules2021222324252627. Of these numerous candidates, to date retinoids are the only one that has been widely investigated in the clinical field (Table 4).…”
Section: Drug Therapies To Regenerate the Damaged Lung In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…In IPF patients, there are scant data regarding the localization of FGF-2 in the lungs. However, the expression of FGF-2 mRNA has been reported to be upregulated in BLM-treated lungs in mice [57]. Although immunohistochemical staining has been reported to show the expression of FGF-2 in inflammatory cells, the role of the FGF-2/FGFR axis in mouse models of lung fibrosis remains unclear.…”
Section: Fgf and Fgf Receptorsmentioning
confidence: 99%
“…Ju et al reported that the administration of soluble FGFR2c ectodomain significantly reduces the extent of lung fibrosis in TGF-Ī²-induced lung fibrosis mice [58]. However, Guzy et al recently reported that Fgf2 ƀ/ƀ mice show increased mortality due to epithelial injury induced by BLM without any effects on lung fibrosis [57]. At present, it is not possible to draw firm conclusions regarding the role of FGF-2 in the pathogenesis of pulmonary fibrosis in mice or in humans.…”
Section: Fgf and Fgf Receptorsmentioning
confidence: 99%